From Oblivion to Reappearance: A Multi-Faceted Evaluation of the Sustainability of Folk Music in Yunnan Province of China - Jia Kuang; Lan He (SAGE Open, 2022)
The Southwestern Chinese province of Yunnan is the home to a plethora of traditional music, folk songs, and ethnic musical instruments with 24 local folk music items included in the national intangible cultural heritage list and extended list. In this article, the authors intend to delve into the issue of Yunnan folk music protection from the perspective of cultural sustainability theory. With an in-depth qualitative analysis of the data on the protection of 24 folk music items of Yunnan, the achievement, impact, and challenges of the current safeguarding efforts are revealed. The findings suggest that: 1. Government agencies at all levels have a dominant influence on the protection effort. 2. The local community, musicians, culture bearers, troupes, clubs, and social organizations form the “brick and mortar” of the folk music sustainability system. 3. The current reappearance or resurface of certain folk music items is a significant step toward truly reviving the folk music items in the future.